Standing in Your Peer’s Shoes Hurts Your Feats: The Self-Others Discrepancy in Risk Attitude and Impulsivity - Białaszek, Wojciech; Bakun, Piotr; McGoun, Elton; Zielonka, Piotr (Frontiers in Psychology, 2016)
It is often a good strategy to “stand in the other person’s shoes” to see a situation from a different perspective. People frequently attempt to infer what someone else would recommend when no advisor is available to help with a decision. Such situations commonly concern intertemporal or risky choices, and the usual assumption is that lay people make such decisions differently than experts do. The aim of our study was to determine what intertemporal and risky decisions people make when they take their own perspective, the perspective of a peer, and the perspectives of an expert or an entrepreneur. In a series of three experiments using a between-subject design, we found that taking the peer’s perspective made participants behave more impulsively and more risk aversely in relation to the participants’ own perspectives and in relation to their perceptions of experts and entrepreneurs perspectives. Taking an expert’s or an entrepreneur’s perspective did not change participants’ own intertemporal and risky decisions. We explain the findings using the risk as value and the lesser mind theories. Imagining the opponent’s perspective in a negotiation as one is advised to do might inadvertently lead to problems because we always see her as more impulsive and more risk averse than she really is.